1971
DOI: 10.1159/000179946
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects of Uraemic Polyneuropathy

Abstract: In order to establish the relationship between uraemic polyneuropathy and impairment of renal function, 83 patients with severe renal insufficiency not treated by maintenance dialysis were neurologically examined, most of them repeatedly in the course of their disease. Signs of neuropathy were found only when the creatinine clearance was 5 ml/min or less. The risk of incapacitating neuropathy was present in patients with a creatinine clearance of 3 ml/min or less. Polyneuropathy was found most frequently in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1972
1972
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…The high incidence of impaired nerve function before dialysis, especially of slowed nerve conduc-tion, is consistent with most comparable reports (3, 5,7,8,9,10,12,21). This was also expected from the strong correlation with the kidney function (&) previously reported (17).…”
Section: Discussionsupporting
confidence: 91%
“…The high incidence of impaired nerve function before dialysis, especially of slowed nerve conduc-tion, is consistent with most comparable reports (3, 5,7,8,9,10,12,21). This was also expected from the strong correlation with the kidney function (&) previously reported (17).…”
Section: Discussionsupporting
confidence: 91%
“…This inquiry was used by the present authors in earlier investigations on industrial workers exposed to carbon disulfide (25) and lead (26,27). The examined persons were thus questioned as to the occurrence of restless legs (6,24), muscle cramps, pain in the extremities, distal paresthesia and numbness, and paresis. For the evaluation of neurasthenia and polyneuropathy symptoms the same standardized criteria were used as in our earlier investigations on industrial workers, i.e., a symptom was considered "positive" when the subject experienced it at a frequency exceeding once a month.…”
Section: Subject Of Evaluationmentioning
confidence: 99%
“…These findings corroborated our earlier observations [8] according to which the red cell TKA in uremia was normal or occasion ally higher than normal. Jennekens et al [4] also found that the TKA was normal in uremia, although the patients were affected with neuritis. Rizzo and V arasi [13] found that the TKA in uremia was significantly higher than in the controls, but that in the former the so-called TPP effect was low, indicating that uremia involved no thiamine deficiency.…”
Section: Discussionmentioning
confidence: 93%